"The role of Quranic schools in building the national character: a study from the viewpoint of those in charge of Quranic schools at the Guidance and Reform Association (Bou-Saada) Field study at the Koranic School of the Association of Guidance and Refor - louglaithi , zayan; djaballah, zahia (Journal of Social Sciences and Humanities, 2021)
The study aimed to identify the role of Quranic schools in building the personality of the Algerian individual, and if there is a relationship between the programs of Quranic schools, such as the revival of Feasts, religious ceremonies, preaching, and religious guidance provided by the Quranic school in building the Algerian character. The problem of study was determined in the following question: Are there statistically significant differences between the sociological role of Quranic schools and building the national character? To achieve the objectives of the study, the descriptive analytical method was used on a random sample of those in charge of the Quranic schools of the Guidance and Reform Association in Bou-Saada, and The number of individuals in the sample reached 40 of those in charge of the Qur’anic schools of the Guidance and Reform Association in Bou-Saada, with various jobs. The results of the study came as follows: There is a statistically significant relationship between the socio-educational role of Quranic schools and the building of the Algerian national character in the Quranic schools of the Association for Reform and Guidance in Bou-Saada. It was also reached that the Quranic School contributes effectively to the transmission of various social values of children and youth as well as the educational material that its progress contributes to providing the learner with various moral values stemming from the authenticity of Algerian society. The study recommended that a greater role be given to Quranic schools in the community and support for Quranic schools (material and moral support) by the competent authorities, given what these schools offer to society